2008
DOI: 10.1002/polb.21472
|View full text |Cite
|
Sign up to set email alerts
|

Oriented crystallization of poly(L‐lactic acid) in uniaxially oriented blends with poly(vinylidene fluoride)

Abstract: This article describes the oriented crystallization of poly(L-lactic acid) (PLLA) in uniaxially oriented blends with poly(vinylidene fluoride) (PVDF). Uniaxially drawn films of PLLA/PVDF blend with fixed ends were heat-treated in two ways to crystallize PLLA in oriented blend films. The crystal orientation of PLLA depended upon the heat-treatment process. The crystal c-axis of the a form crystal of PLLA was highly oriented in the drawing direction in a sample cold-crystallized at T c ¼ 120 8C, whereas the tilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The melting peak of PLA at 156°C, labeled as T m 1 , becomes more and more obvious with increasing content of PLA. Besides, the glass transition temperature of PLA appears at 60°C obviously, which confirms the immiscibility between PLA and PVDF, which has also been found by Li et al in PVDF/PLLA blends 29. For stretched neat PVDF, there is a strong peak (labeled as T 2 ) at 163°C and a weak shoulder (labeled as T 3 ) locates at 168°C, respectively.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The melting peak of PLA at 156°C, labeled as T m 1 , becomes more and more obvious with increasing content of PLA. Besides, the glass transition temperature of PLA appears at 60°C obviously, which confirms the immiscibility between PLA and PVDF, which has also been found by Li et al in PVDF/PLLA blends 29. For stretched neat PVDF, there is a strong peak (labeled as T 2 ) at 163°C and a weak shoulder (labeled as T 3 ) locates at 168°C, respectively.…”
Section: Resultssupporting
confidence: 83%
“…PVDF/PLA blends have caught the interest of researchers recently. Kaito et al29 found that oriented crystallization of α phase of PLLA in PVDF/PLLA blends occurred in the stretched domains of PLLA with diameters of 0.5–0.2 μm and they ascribed it to the heteroepitaxy of the (200)/(110) axes of the α crystals of PLLA along the (201)/(111) axes of the β crystals of PVDF due to lattice matching of d 100 (PLLA) ≈ 5 d 201 (PVDF). Chen et al30 also found the transition of crystalline phase from α‐ to β‐form of PVDF for the spun PVDF/PLA samples.…”
Section: Introductionmentioning
confidence: 99%
“…In study 10 (melt compounding), 1.6 wt.% MWNT apparently had no influence on a reflections, reflection (2 0 0) b did not appear, instead reflection (0 0 1) b was reported at $30°. This reflection has also been reported (at $35°) for heat treated and stretched PVDF film [18], and at 31°for intercalated nanoclay/PVDF (study 2). In study 11 (melt and solution compounding), a range of MWNT contents was used including small contents of 0.1 and 0.5 wt.%.…”
Section: Nanofilled Pvdf Filmssupporting
confidence: 56%
“…The miscibility is a key factor to affect structural formation and resulted properties of the blends. PVDF is immiscible with most polymers due to lack of enough chain interactions . The second component is dispersed as micron droplets in the PVDF matrix, and there exists remarkable phase interface between two components.…”
Section: Introductionmentioning
confidence: 99%